Investigation of the Possibility of Cider Production in Armenia Using Different Dry Active Yeasts - Iskandaryan, A. Kh.; Mikaelyan, M. N.; Gevorgyan, E. R. (ՀԱԱՀ հիմնադրամ)
The volume of production and consumption of cider as a low alcoholic and soft drink is increasing year by year. Being a part of the global economy, a similar trend is also noticeable among a smaller scale Armenian producers and consumers. During this research we studied the physicochemical parameters of apple juice and ready-made cider obtained from apple varieties common in Armenia. Fermentation was carried out with four different yeasts intended for cider production and one control sample. The aim was to reveal the effect of each yeast on the quantitative and qualitative characteristics of the final cider.
Keywords: Food Science and Technology